1984
DOI: 10.1136/thx.39.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of chest wall motion in patients with chronic airflow obstruction.

Abstract: Forty patients with severe chronic stable airflow obstruction and hyperinflation were studied to assess patterns of abnormal chest wall motion and their frequency. Dimensional changes were measured during tidal breathing, four pairs of magnetometers being used to record anteroposterior diameters of ribcage and abdomen and two lateral diameters of the ribcage. Chest wall movements were qualitatively normal in only five patients. Three main types of abnormality were found and 13 subjects had two or more abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 14 publications
1
53
1
2
Order By: Relevance
“…Maximal phrenic nerve stimulation maximally activates the diaphragm, allowing for increased muscle shortening and dome descent with a reduced diaphragm load given that the active muscles of the rib cage are silent. This condition is similar to those during chronic obstructive pulmonary disease (COPD) where diaphragm load is decreased and the rib cage is expanded (8,18). In this study, we demonstrated that during bilateral phrenic nerve stimulation, the percentage of diaphragm muscle shortening, abdominal VD, and total VD values were two-to three-fold greater than those that occurred during submaximal diaphragm activation.…”
Section: Discussionsupporting
confidence: 50%
“…Maximal phrenic nerve stimulation maximally activates the diaphragm, allowing for increased muscle shortening and dome descent with a reduced diaphragm load given that the active muscles of the rib cage are silent. This condition is similar to those during chronic obstructive pulmonary disease (COPD) where diaphragm load is decreased and the rib cage is expanded (8,18). In this study, we demonstrated that during bilateral phrenic nerve stimulation, the percentage of diaphragm muscle shortening, abdominal VD, and total VD values were two-to three-fold greater than those that occurred during submaximal diaphragm activation.…”
Section: Discussionsupporting
confidence: 50%
“…The best recognized distortion is lateral inspiratory paradox of the rib margin, otherwise known as Hoover's sign [10]. In one study [5], this was detectable in as many as 31 of 40 otherwise unselected patients with COPD. Paradoxical lateral motion typically develops with the onset of inspiration, continuing to late inspiration, sometimes with an increase in the dimension in the terminal part of inspiration.…”
Section: Series 'Lung Hyperinflation In Airway Obstruction' Edited Bymentioning
confidence: 99%
“…They suggested that the impression of increased AP diameter of the chest was actually the result of a reduced AP diameter of the abdomen, due to wasting. On the other hand, GILMARTIN and GIBSON [5] measured the dimensions of the rib cage at FRC and showed an increase in the ratio of AP to lateral diameters, i.e. the rib cage was more circular in cross-section than in normal subjects.…”
Section: Series 'Lung Hyperinflation In Airway Obstruction' Edited Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Breathing is often the first vital sign to alter in an acutely deteriorating patient, because changes in breathing pattern accompany many respiratory [1][2][3] and non-respiratory disorders [4]. Abnormal breathing patterns have also been observed in patients with chronic respiratory diseases such as Chronic Obstructive Pulmonary Disease (COPD) [5], bronchiectasis [6] and asthma [7].…”
Section: Introductionmentioning
confidence: 99%